"This Is Not Just a Story About New York" - Refiguring Spaces through Innovation - Steets, Silke (Sociologica, 2022)
This essay explores how Sharon Zukin conceptualizes the relationship between space and place in her analysis of how "innovation" is embedded in the political economy, culture, and geography of New York City. Whereas Zukin takes New York as a testing ground for the re-organization of capitalism around the world, I propose to conceptualize the capitalist logic of place production in more complex terms by adding two extensions. First, I propose a more thorough examination of the cultural logic of the tech industry in contrast to the creative industry and a focus on its specific forms of place-making. Second, I will argue for thinking processes of the spatialization of social phenomena in a multidimensional and polymorphic way. To this end, I argue for an understanding of social change as a "refiguration of spaces".
CRIS-Team WoS Importer:2023-02-03